THE STUDENTS’ PERCEPTION IN LEARNING VOCABULARY THROUGH ENGLISH RELIGIOUS SONG LYRICS AT CONVENTUAL FRANCISCAN POSTULANCY-INDONESIA - merry susanty br tarigan; Natalia Widya Pasca Tarigan; Emma Martina Br. Pakpahan Br. Pakpahan (English Language Teaching Prima Journal (ELT), 2026)
The objective of the study is to find out the students’ perceptions in learning vocabulary through English religious song lyrics. This study was conducted at Conventual Franciscan Postulancy-Indonesia. The research was designed by using Qualitative Descriptive Method. It involved 20 students of academic year 2025-2026 as the subjects of the study. The data was collected by using Questionnaire (Likert Scale) and Interview. The research findings show that most of the students had good perceptions in learning vocabulary through English religious song lyrics. Furthermore, they also found that song lyrics can be used as one of the enjoyable media in learning. The result of questionnaire had shown that the percentage from students who agreed that song lyrics can be used as one of the most important media in learning vocabulary which can motivate them during class was most of the students agreed. Through the data of interview can be also seen that most of the students gave positive responds or perceptions in using song lyrics during vocabulary class. It can be stated that this media can help the students in learning vocabulary and establishing their mood during class.